2022
DOI: 10.3389/fpsyg.2022.795770
|View full text |Cite
|
Sign up to set email alerts
|

Further Investigation of the Dimensionality of the Questionnaire for Eudaimonic Well-Being

Abstract: The dimensionality of the Questionnaire for Eudaimonic Well-Being (QEWB) has been a topic of debate and divergent findings in the literature up to date. This study investigated the factor structure and measurement invariance of the QEWB in four culturally diverse South African samples using confirmatory factor analysis (CFA), bifactor CFA, exploratory structural equation modelling (ESEM), and bifactor ESEM. Three student samples completed the English (n = 326), Afrikaans (n = 478), or Setswana (n = 260) versio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Confirmatory Factor Analysis (CFA) [ 14 ] was conducted to test the internal consistency [ 15 ]. As the CFA is performed based on structural equation modelling (SEM) [ 16 ], sampling followed the SEM sampling calculation method, where the sample size should be at least 200 [ 17 ]. Also, it was suggested that the sample of the CFA should be between 100 and 200 [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Confirmatory Factor Analysis (CFA) [ 14 ] was conducted to test the internal consistency [ 15 ]. As the CFA is performed based on structural equation modelling (SEM) [ 16 ], sampling followed the SEM sampling calculation method, where the sample size should be at least 200 [ 17 ]. Also, it was suggested that the sample of the CFA should be between 100 and 200 [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…We could not find a translation into German and we thus offer a translation into German of our own (s. Appendix A ). Various authors have shown in different cultural contexts that the QEWB has good psychometric properties with regard to surveying students [ 2 , 30 , 33 , 34 , 35 ], but also adults [ 29 , 32 , 36 ].…”
Section: Introductionmentioning
confidence: 99%